الشفافية في جهاز الرقابة المالية والإدارية بسلطنة عمان: المرتكزات والأبعاد: Transparency in the Financial and Administrative Control Authority in the Sultanate of Oman: Pillars and Dimensions - أحمد عبد الله سالم المشايخي; محمد نذري محمد نور (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
ملخص تهدف الدراسة إلى التعرف على الشفافية في جهاز الرقابة المالية والإدارية بسلطنة عمان. وتكمن مشكلة الدراسة في تدني وضع المؤسسات العمانية في مؤشر مدركات الفساد العالمي، الأمر الذي يعكس انتشار الفساد المالي والإداري بجهاز الرقابة المالاية والإدارية بسلطنة عمان. وتبرز أهمية الدراسة في تسليط الضوء على الشفافية في جهاز الرقابة المالية والإدارية بسلطنة عمان. واتبعت الدراسة المنهج الوصفي التحليلي لوصف وتحليل الشفافية في جهاز الرقابة المالية والإدارية بسلطنة عمان. ولقد توصلت الدراسة إلى العديد من النتائج من بينها أن جهاز الرقابة المالية والإدارية يحاول تطبيق معايير الحوكمة وفقاً للتعليمات الصادرة بهذا الشأن. ولقد أوضحت النتائج أن من أهم أبعاد الشفافية هي إمكانية الفصل بين السلطات وممارسة الشفافية في مجالات الحياة العامة وتفعيل القانون. كما أوضحت النتائج أن مرتكزات الشفافية هي وضوح قواعد العمل في المؤسسات وأبعاد الشخصيات المشكوك فيها عن العمل المالي والإداري وترشيد الإستهلاك وضمان الحصول على المعلومات بجهاز الرقابة المالية والإدارية بسلطنة عمان. وخلصت النتائج إلى أن تطبيق الشفافية ساهم بشكل كبير في تعزيز حرية الحصول على المعلومات، كما أن تقارير الهيئات الرقابية عن الأوضاع داخل المؤسسات يتناولها الجمهور بالكثير من الاهتمام الأمر الذي يشير إلى أهمية الدور الإعلامي البارز الذي تمارسه المؤسسات الرقابية في سبيل تعزيز دور الشفافية. ولقد أوصت الدراسة بضرورة التوسع في تطبيق عناصر الشفافية في جهاز الرقابة المالية والإدارية بسلطنة عمان. كما أوصت الدراسة أن ممارسة الشفافية تساهم في شيوع مزيد من الحريات في المجتمع إلا أنه يرى أن تطبيق الشفافية لايجب أن يكون قاصراً على الموظف العام في المؤسسات فقط دون النظر إلى القيادات العليا، فقد تكون تلك القيادات أحد أسباب الفساد المالي والإداري. كما أوصت الدراسة بأن الجهات الرقابية لديها العديد من الأسس والمعايير في مسألة العقاب والمحاسبة دون الإخلال بحقوق الموظف وكذلك البحث في اسباب تحايله وحصوله على أموال بغير حق من المؤسسة التي يعمل بها. Abstract The study aims to identify transparency in the Financial and Administrative Control Authority in the Sultanate of Oman. The problem of the study lies in the low status of Omani institutions in the Global Corruption Perceptions Index, which reflects the spread of financial and administrative corruption in the Financial and Administrative Control Authority in the Sultanate of Oman. The study highlights the importance of shedding light on transparency in the Financial and Administrative Control Authority in the Sultanate of Oman. The study followed the descriptive analytical approach to describe and analyze transparency in the Financial and Administrative Control Authority in the Sultanate of Oman. The study reached many results, including that the Financial and Administrative Control Authority is trying to apply governance standards in accordance with the instructions issued in this regard. The results showed that one of the most important dimensions of transparency is the possibility of separating powers, practicing transparency in the areas of public life, and activating the law. The results also showed that the pillars of transparency are clarity of work rules in institutions, the dimensions of suspicious personalities from financial and administrative work, rationalization of consumption, and ensuring access to information by the Financial and Administrative Control Authority in the Sultanate of Oman. The results concluded that the application of transparency greatly contributed to enhancing the freedom of access to information, and the reports of the supervisory bodies on the situation inside the institutions received a lot of attention from the public, which indicates the importance of the prominent media role played by the supervisory institutions in order to enhance the role of transparency. The study recommended the need to expand the application of transparency elements in the financial and administrative control body in the Sultanate of Oman. The study also recommended that the practice of transparency contributes to the spread of more freedoms in society, but it is of the opinion that the application of transparency should not be limited to the public employee in institutions only without looking at the higher leaders, as these leaders may be one of the causes of financial and administrative corruption. The study also recommended that the supervisory authorities have many foundations and standards in the matter of punishment and accountability without prejudice to the rights of the employee, as well as researching the reasons for his fraud and obtaining illegal funds from the institution in which he works.